2013
DOI: 10.1016/j.pmrj.2013.03.025
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Combined Trunk and Gluteal Neuromuscular Electrical Stimulation on Posture and Tissue Health in Spinal Cord Injury

Abstract: Trunk and gluteal stimulation acutely corrects anterior/posterior IP distribution, improving regional tissue health for sacral sitters. This correction requires constant application of NMES. The potential for positive changes in tissue health would be maximized by regular NMES use incorporating weight shifting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
(33 reference statements)
1
16
0
Order By: Relevance
“…This study demonstrates that administering NMES in conjunction with physical therapy has better results than physical therapy alone for strengthening muscles. NMES has not been used very often in the treatment of clubfoot, but it has been used as part of the treatment for many other diseases and in otherwise healthy people, especially athletes, and all of the studies have shown, as ours did, that there is an increase in strength of different muscles after treatment (13,(15)(16)(17)(18)(19). However, for the CC treatment, there is only one report to date, and its sample was small (n = 8) compared to the current contribution (n = 20) (20).…”
Section: Discussionsupporting
confidence: 54%
“…This study demonstrates that administering NMES in conjunction with physical therapy has better results than physical therapy alone for strengthening muscles. NMES has not been used very often in the treatment of clubfoot, but it has been used as part of the treatment for many other diseases and in otherwise healthy people, especially athletes, and all of the studies have shown, as ours did, that there is an increase in strength of different muscles after treatment (13,(15)(16)(17)(18)(19). However, for the CC treatment, there is only one report to date, and its sample was small (n = 8) compared to the current contribution (n = 20) (20).…”
Section: Discussionsupporting
confidence: 54%
“…Other types of ES identified for PU prevention through this review included a custom-made garment with built-in electrodes, 48 the electrical current delivered through a sacral anterior nerve root stimulator (SARS) implant, 44,45 or alternatively, via implanted intramuscular electrodes. 41,51,52 Stimulation sites Eight out of 16 studies stimulated gluteal muscles alone, and five trials activated gluteal muscles together with other muscle groups, e.g. quadriceps, hamstrings, and lumber spinal muscles.…”
Section: Intervention Featuresmentioning
confidence: 99%
“…Among 32 elderly wheelchair users, seating interface pressure was significantly higher among those who developed pressure ulcers during the trial compared to those who did not. Others have used IPM to assess tissue viability in response to postural interventions among people with SCI [16]. Various IPM metrics have been reported in the literature, including average pressure, peak pressure, peak pressure index, peak pressure gradient, peak pressure ratio, and dispersion index [2, 17, 18].…”
Section: Introductionmentioning
confidence: 99%